2019
DOI: 10.7554/elife.45413
|View full text |Cite
|
Sign up to set email alerts
|

Junction Mapper is a novel computer vision tool to decipher cell–cell contact phenotypes

Abstract: Stable cell–cell contacts underpin tissue architecture and organization. Quantification of junctions of mammalian epithelia requires laborious manual measurements that are a major roadblock for mechanistic studies. We designed Junction Mapper as an open access, semi-automated software that defines the status of adhesiveness via the simultaneous measurement of pre-defined parameters at cell–cell contacts. It identifies contacting interfaces and corners with minimal user input and quantifies length, area and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…Assessing IEJ at the single cell level is key to highlight subtle nuances in inter-endothelial cells connectivity within the same monolayer. Nonetheless, measuring and classifying junctional signal by image analysis is technically challenging and no currently available software is able to evaluate multiple images in a standardised way 29,30 . To overcome this obstacle, we have implemented within ECPT a junction analysis method (Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing IEJ at the single cell level is key to highlight subtle nuances in inter-endothelial cells connectivity within the same monolayer. Nonetheless, measuring and classifying junctional signal by image analysis is technically challenging and no currently available software is able to evaluate multiple images in a standardised way 29,30 . To overcome this obstacle, we have implemented within ECPT a junction analysis method (Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although VE-cadherin junction are dynamic, previous studies showed the possibility to characterize the junction patterning with image analysis 25, 26 . However, most work carried on HUVEC did not study the differences in different organ-specific EC and did not study single-cell level heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other GTPase disruption of keratinocyte junctions ( Braga et al, 2000 ; Brezovjakova et al, 2019 ; Frasa et al, 2010 ), Rac1 activation induces a striking phenotype: Cells flatten out with elongation of the contacting interface between neighbors (this work), and thickening of cadherin staining in the middle of junctions ( Lozano et al, 2008 ). The progressive disappearance of cadherin staining from cell corners suggests that E-cadherin delivery to junctions is misdirected to the center of contacts.…”
Section: Discussionmentioning
confidence: 76%
“…Reduced Pearson coefficient values may reflect the contribution of the cytosolic pool of catenins associated with distinct partners (i.e., not on vesicles). Unfortunately, the striking Rac1-specific phenotype at junctions (with augmented fluorescence signal in the middle of contacts; Lozano et al, 2008 ) makes it challenging to compare the relative cadherin-catenin association at junctions with the vesicular pool ( Brezovjakova et al, 2019 ). Similar analyses with E-cadherin immunoprecipitation from transduced (TAT-Rac1 Q61L ) or transfected cells (myc-Rac1 Q61L ) lysates did not show the release of catenins from the complex ( Fig.…”
Section: Resultsmentioning
confidence: 99%